Film production technique : creating the accomplished image - Mamer, Bruce, 1952- (Cengage Learning, 2014)
"Film Production Technique, 6e", delivers a technical and aesthetic introduction to media production that couples video production techniques with strong emphasis on incorporating motion picture film into a project's workflow."
Terminologický slovník
Keywords: filmová výroba; kinematografie; film production industry; cinematography; příručky; handbooks, manuals, etc